NEWLY DESCRIBED AND NEWLY RECORDED OF INFRASPECIFIC TAXA OF MUSA BORNEENSIS BECC. (MUSACEAE) FROM SULAWESI, INDONESIA - Lulut Dwi Sulistyaningsih (REINWARDTIA, 2017)
SULISTYANINGSIH, L. D. 2016. Newly described and newly recorded of infraspecific taxa of Musa borneensis Becc. (Musaceae) from Sulawesi, Indonesia. Reinwardtia 16 (1): 19 - 24. - A new variety of Musa borneensis, M. borneensis var. donggalaensis Sulis. is proposed based upon specimens from Donggala, Central Sulawesi, Indonesia. Endemic status of M. borneensis was rejected. The description, distribution map and the identification key are provided.